Mucopolysaccharidosis IIIB, cerebral vasculopathy and recurrent subdural hematoma - Aydin, Mustafa; Akarsu, Saadet; Kabakus, Nimet; Akpolat, Nusret (Springer India, 2006)
Mucopolysaccharidoses are characterized by involvement of multiple organs, including blood vessels. We present a case of mucopolysaccharidosis IIIB admitted with recurrent subdural hematoma; further evaluation and dural biopsy revealed an association with cerebral vasculopathy.
Keywords: mucopolysaccharidosis IIIB; subdural hematoma; vasculopathy